OPTIMALISASI PEMANFAATAN ASET TANAH DAN BANGUNAN MILIK PEMERINTAH KOTA BANDA ACEH - Ibrahim, Fadillah; Ridwan, Ridwan (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2020)
This research aims to identify and analyze the optimization of the utilization of land and building assets belonging to the Banda Aceh City Government, especially in market buildings to increase local revenue. Research on the optimization of the use of land and building assets owned by the Banda Aceh City Government uses a qualitative descriptive approach, the data used are secondary data in the form of financial reports in the Banda Aceh City Government during 2015-2018, and also primary data using interview techniques. The results of this study indicate that the contribution rate of asset utilization from 2015-2018 is still not optimal for increasing PAD and below 1% with an average of 0.045%. Meanwhile, the level of contribution to the market retribution services is still not optimal for increasing PAD. seen the contribution of the realization of market service levies to local revenue in 2015 amounted to 0.092%. 2016 The contribution of realization of market service fees was 0.083% Likewise in 2017, the contribution of market retribution of services was the same as in 2016, namely 0.083%. However, in 2018, the contribution to the realization of market services was higher than the previous year, the amounting to 0.094%